Sunscreen heat insulation composite material and preparation method thereof
By using zinc oxide/copolyester composite materials and nano copper sulfide in thermal insulation materials, the problem of poor compatibility between nanometal oxide and resin is solved, and the ultraviolet and thermal insulation properties of the composite materials are improved, thus achieving the Excellent water resistance and bonding properties.
Patent Information
- Application Number
- CN202411393704.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When the existing thermal insulation materials prepare the thermal insulation layer, the nanometal oxides and the matrix resin of the thermal insulation layer are poor, which affects the performance of the composite film and has poor ultraviolet shielding performance, which limits its application.
Zinc oxide/copolyester composite material is used as the intermediate layer material, and the design of photocuring surface and glue layer material is combined with nano copper sulfide as the thermal insulation additive to improve the UV resistance and thermal insulation properties of the composite material.
The excellent UV resistance, heat insulation, water resistance and adhesive properties of the composite material are achieved, and the overall performance of the material is improved.
Smart Images

Figure CN119264825A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of multilayer materials, and in particular to a sun-proof and heat-insulating composite material and a preparation method thereof. Background Art
[0002] Thermal insulation materials can achieve the effect of thermal insulation by reflecting and refracting sunlight, reducing the absorption of solar radiation energy by the material surface. According to different thermal insulation mechanisms and methods, thermal insulation materials can be divided into: barrier thermal insulation materials, reflective thermal insulation materials and radiation thermal insulation materials. Traditional thermal insulation materials usually achieve thermal insulation by increasing the thickness of the material to reduce thermal conductivity, reduce convection conduction and radiation heat transfer, or by splicing with inorganic thermal insulation materials. Thermal insulation materials based on polymer resins have problems such as poor UV shielding performance, which limits their application.
[0003] Prior art such as Chinese patent CN102765224A discloses an anti-UV high heat-insulating window film, which has an anti-scratch layer, a transparent film substrate layer, a heat-insulating layer composed of a UV-curing coating and nano-metal oxides, a UV blocking layer, a pressure-sensitive adhesive layer and a release film layer. It has the characteristics of high UV light blocking rate and high heat-insulating efficiency. However, the nano-metal oxides used in the preparation of the heat-insulating layer have poor compatibility with the heat-insulating layer matrix resin and are easy to agglomerate, affecting the performance of the composite film. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a sunscreen and heat-insulating composite material and a preparation method thereof. The composite material has excellent anti-ultraviolet and heat-insulating properties, and good water resistance and bonding properties.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a sun-proof and heat-insulating composite material comprises the following steps:
[0007] Step 1: preparing the surface layer / middle layer composite material and the adhesive layer material;
[0008] The surface layer / middle layer composite material is prepared by the following steps:
[0009] Step (1), mixing and dispersing polyethylene glycol and nano zinc oxide, adding 2,4-diphenylcyclobutane-1,3-dicarboxylic acid, benzophenone-4,4-dicarboxylic acid and stannous octoate, reacting, and continuing the reaction after the reaction is completed, and obtaining a zinc oxide / copolyester composite material after the reaction is completed;
[0010] The zinc oxide / copolyester composite material is mixed with polyethylene terephthalate, melt-extruded, hot-pressed into a film, and quenched to obtain an intermediate layer material;
[0011] Step (2), epoxy acrylate, γ-methacryloxypropyl trimethoxysilane, hexafluorobutyl acrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, a photoinitiator, and acetone are uniformly mixed to obtain a surface layer material, the surface layer material is coated on one side of the middle layer material, and light-cured to obtain a surface layer / middle layer composite material;
[0012] The adhesive layer material is prepared by the following steps:
[0013] Step (1), mixing hexafluorobutanol, isophorone diisocyanate, dibutyltin dilaurate and acetone uniformly, reacting, cooling to room temperature after the reaction, adding diethanolamine, and continuing the reaction, and after the reaction, removing the solvent acetone by rotary evaporation to obtain a fluorine-containing diol;
[0014] Step (2), mixing isophorone diisocyanate, polycarbonate diol and acetone, reacting, adding dibutyltin dilaurate, fluorinated diol and S-binaphthol after the reaction, continuing the reaction, cooling after the reaction, adding p-hydroxyanisole and hydroxyethyl acrylate in sequence, reacting again, and removing the solvent acetone by rotary evaporation after the reaction to obtain polyurethane acrylate;
[0015] Step (3), mixing polyurethane acrylate, heat insulation additive, maleic anhydride modified polyvinyl butyral, trimethylolpropane triacrylate, 4-(N-maleimido) benzophenone, and acetone to obtain a glue layer material;
[0016] The thermal insulation additive is prepared by the following steps:
[0017] Mix and dissolve 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetrahydrofuran, add formaldehyde aqueous solution, stir, dropwise add catechol solution, react after the dropwise addition is complete, and after the reaction is complete, remove the solvent tetrahydrofuran by rotary evaporation, purify, and obtain siloxane-based benzoxazine;
[0018] The nano copper sulfide, siloxane benzoxazine, dimethyl silicone oil and dichloromethane are mixed, ultrasonically dispersed, reacted, and after the reaction is completed, the reaction is continued. After the reaction is completed, the reaction is cooled, filtered, washed and dried to obtain a heat insulation additive;
[0019] Wherein, the maleic anhydride modified polyvinyl butyral is prepared by the following steps:
[0020] Polyvinyl butyral, maleic anhydride, N,N-dimethylbenzylamine and acetone are mixed and reacted, and after the reaction is completed, the solvent acetone is removed by rotary evaporation to obtain maleic anhydride modified polyvinyl butyral;
[0021] Step 2: coating the adhesive layer material on the side of the surface layer / middle layer composite material away from the surface layer material (i.e. the side of the middle layer material not coated with the surface layer material), and drying after coating to obtain a sunscreen and heat insulation composite material.
[0022] Preferably, when preparing the surface layer / middle layer composite material in step one, in step (1): the molar ratio of polyethylene glycol, 2,4-diphenylcyclobutane-1,3-dicarboxylic acid and benzophenone-4,4-dicarboxylic acid is 5:1-1.5:3.5-4, the amount of nano zinc oxide added is 8-10% of the mass of polyethylene glycol, and the amount of stannous octoate added is 3% of the mass of polyethylene glycol; the reaction conditions are: reacting in a nitrogen atmosphere at a temperature of 175-185°C for 4-5h; and the continued reaction conditions are: continuing the reaction at a vacuum degree of 220-240Pa and a temperature of 200-220°C for 1-1.5h.
[0023] Preferably, when preparing the surface layer / middle layer composite material in step one, in step (1): the mass ratio of the zinc oxide / copolyester composite material to the polyethylene terephthalate is 40-50:50; the melt extrusion conditions are: melt extrusion at a temperature of 270-275°C; the hot pressing film forming conditions are: placing in a mold and hot pressing into a film at a pressure of 5-10MPa and a temperature of 270-280°C through a flat plate vulcanizer; the thickness of the middle layer material is 90-100μm.
[0024] Preferably, when preparing the surface layer / middle layer composite material in step one, in step (2): the mass ratio of epoxy acrylate, γ-methacryloxypropyltrimethoxysilane, hexafluorobutyl acrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, photoinitiator, and acetone is 100:8-10:6-8:10-15:10-15:3-4:20-25; the photocuring conditions are: photocuring for 1-2 min under ultraviolet light with a wavelength of 405 nm and a temperature of 80-90° C.; and the thickness of the surface layer / middle layer composite material is 95-105 μm.
[0025] Preferably, when preparing the adhesive layer material in step one, in step (1): the molar ratio of hexafluorobutanol, isophorone diisocyanate and diethanolamine is 0.9-1:1:0.9-1, the amount of dibutyltin dilaurate added is 2-3% of the mass of hexafluorobutanol, and the amount of acetone added is 50-60% of the mass of hexafluorobutanol; the reaction conditions are: reacting for 3-4 hours at a temperature of 70-80°C in a nitrogen atmosphere; and the continued reaction conditions are: continuing the reaction at room temperature for 20-30 minutes.
[0026] Preferably, when preparing the adhesive layer material in step 1, in step (2): the mass ratio of isophorone diisocyanate, polycarbonate diol, fluorinated diol, S-binaphthol, dibutyltin dilaurate, acetone, p-hydroxyanisole, and hydroxyethyl acrylate is 110-120:150-160:75-80:28-33:7-8:200-220:1.5-2:15-20; the reaction conditions are: reacting at a temperature of 70-80°C in a nitrogen atmosphere for 1.5-2h; the continued reaction conditions are: continuing the reaction at a temperature of 70-80°C for 3-4h; and the second reaction conditions are: reacting again at a temperature of 50-60°C for 2-3h.
[0027] Preferably, when preparing the adhesive layer material in step one, in step (3): the mass ratio of polyurethane acrylate, thermal insulation additive, maleic anhydride modified polyvinyl butyral, trimethylolpropane triacrylate, 4-(N-maleimido)benzophenone, and acetone is 100:8-10:10-15:25-30:2-3:30-40.
[0028] Preferably, when preparing the adhesive layer material in step 1, when preparing the thermal insulation additive: the mass ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetrahydrofuran, formaldehyde aqueous solution, and catechol solution is 2.5-2.8:90-100:3.2-3.5:38-40; the formaldehyde aqueous solution is a 37wt% formaldehyde aqueous solution, and the adding conditions are: adding in a nitrogen atmosphere at a temperature of 0-2°C, and stirring for 0.5-1h after adding; the catechol solution is prepared by mixing catechol and tetrahydrofuran in a mass ratio of 1:20, and the dropping time is 15-20min; when preparing siloxane-based benzoxazine, the reaction conditions are: reacting at a temperature of 60-70°C for 5-6h.
[0029] Preferably, the purification operation comprises: taking the crude reaction product obtained after rotary evaporation, adding toluene and water in an amount 4-5 times the mass of the crude reaction product in sequence, separating the liquids, taking the organic phase, adding saturated sodium bicarbonate aqueous solution and saturated sodium chloride aqueous solution in an amount 4-5 times the mass of the crude reaction product in sequence, washing three times, separating the liquids, taking the washed organic phase, adding 20-25wt% of anhydrous sodium sulfate to the washed organic phase for drying, filtering, taking the filtrate, and removing the solvent by rotary evaporation at a temperature of 70-80°C.
[0030] Preferably, when preparing the adhesive layer material in step 1, in step (3), when preparing the thermal insulation additive: the mass ratio of nano copper sulfide, siloxane benzoxazine, dimethyl silicone oil and dichloromethane is 7-8:2-3:10-20:20-30; when preparing the thermal insulation additive, the reaction conditions are: reacting at a temperature of 140-150°C for 4-5h, and the continued reaction conditions are: continuing the reaction at a temperature of 175-185°C for 1-1.5h.
[0031] Preferably, when preparing the adhesive layer material in step 1, in step (3), when preparing maleic anhydride modified polyvinyl butyral: the mass ratio of polyvinyl butyral, maleic anhydride, N,N-dimethylbenzylamine, and acetone is 20-22:10-12:0.3:50-60; and the reaction conditions are: reacting at a temperature of 70-80°C for 4-5h.
[0032] Preferably, in step 2: the coating speed is 5-10 m / min, and the thickness of the adhesive layer material is 15-20 μm.
[0033] Preferably, a sun-proof and heat-insulating composite material is prepared by the method for preparing the sun-proof and heat-insulating composite material as described above.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The invention prepares a zinc oxide / copolyester composite material with ultraviolet absorption effect, adds the composite material into polyethylene terephthalate to prepare an intermediate layer material; coats a wear-resistant and hydrophobic surface layer material on one side of the intermediate layer material to obtain a surface layer / intermediate layer composite material; adds fluorinated diol and S-binaphthol as functional monomers into the preparation process of polyurethane acrylate to obtain polyurethane acrylate with hydrophobic and anti-ultraviolet properties, mixes the polyurethane acrylate with a heat insulation additive, maleic anhydride-modified polyvinyl butyral, active diluent trimethylolpropane triacrylate, polymerizable photoinitiator 4-(N-maleimido) benzophenone and a solvent to obtain a glue layer material, and coats the glue layer material on a side of the surface layer / intermediate layer composite material away from the surface layer material. The obtained sunscreen and heat insulation composite material has excellent anti-ultraviolet and heat insulation properties, and has good water resistance and bonding properties.
[0036] The present invention introduces nano zinc oxide into the polymerization reaction of copolyester by in-situ polymerization, generates an esterification reaction between polyethylene glycol, 2,4-diphenylcyclobutane-1,3-dicarboxylic acid and benzophenone-4,4-dicarboxylic acid to generate a zinc oxide / copolyester composite material, and adds the composite material into polyethylene terephthalate to obtain an intermediate layer material having better ultraviolet resistance and heat resistance. Among them, 2,4-diphenylcyclobutane-1,3-dicarboxylic acid has a double benzene ring structure, which can improve the ultraviolet shielding effect and heat resistance of the material, and benzophenone-4,4-dicarboxylic acid contains a benzophenone group with ultraviolet absorption effect. The two are introduced into the copolyester as polymerization monomers, and the nano zinc oxide with ultraviolet resistance can cooperate with the nano zinc oxide to further improve the ultraviolet resistance and heat resistance of the zinc oxide / copolyester composite material.
[0037] The present invention mixes epoxy acrylate, γ-methacryloxypropyl trimethoxysilane, hexafluorobutyl acrylate, active diluent 1,6-hexanediol diacrylate and trimethylolpropane triacrylate, a photoinitiator and a solvent acetone as a surface layer material. Both γ-methacryloxypropyl trimethoxysilane and hexafluorobutyl acrylate have low surface energy and can improve the hydrophobicity of the material surface. The surface layer material is coated on one side of the middle layer material, and is cross-linked with epoxy acrylate through a photocuring reaction to form a network structure. The wear resistance and hydrophobicity of the prepared surface layer / middle layer composite material are improved.
[0038] The invention allows isophorone diisocyanate, polycarbonate diol, fluorine-containing diol and S-binaphthol to react, and uses hydroxyethyl acrylate to block the end to prepare polyurethane acrylate; wherein the fluorine-containing diol is obtained by reacting hexafluoro-n-butyl alcohol with isophorone diisocyanate and then reacting with diethanolamine again, and the fluorine-containing diol is introduced into the polyurethane acrylate as a diol monomer to improve the hydrophobicity; S-binaphthol has a rigid structure of an aromatic compound and has optical activity, and the introduction of the fluorine-containing diol into the polyurethane acrylate can reduce the infrared emissivity of the material and improve the mechanical properties and heat-resistant and heat-insulating properties of the material;
[0039] The invention uses 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to react with formaldehyde and catechol to generate siloxane-based benzoxazine, which is used as a surface modifier to polymerize on the surface of nano copper sulfide of thermal insulation filler to form a polybenzoxazine structure rich in phenolic hydroxyl groups to obtain a thermal insulation additive; the thermal insulation additive is mixed with polyurethane acrylate, maleic anhydride-modified polyvinyl butyral, active diluent trimethylolpropane triacrylate, polymerizable photoinitiator 4-(N-maleimido) benzophenone, and solvent acetone to obtain a glue layer material; wherein the thermal insulation filler nano copper sulfide in the thermal insulation additive is thermal insulation material. Excellent performance, good heat resistance of polybenzoxazine structure, and rich in phenolic hydroxyl groups, which can form hydrogen bonds with fluorine atom groups in polyurethane acrylate, thereby improving the dispersibility and compatibility of thermal insulation additives in the adhesive layer material; maleic anhydride modified polyvinyl butyral is prepared by the reaction of polyvinyl butyral and maleic anhydride, and the carboxyl group contained therein can improve the bonding performance as a polar group, and the carbon-carbon double bond can participate in the photocuring reaction to improve the comprehensive performance of the adhesive layer material; the adhesive layer material is coated on the side of the surface / middle layer composite material away from the surface material, and the obtained sunscreen and heat insulation composite material has excellent UV resistance and thermal insulation performance, and good water resistance and bonding performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a process flow chart for preparing the sun-proof and heat-insulating composite material in the present invention;
[0041] Figure 2 It is a schematic structural diagram of the sun-proof and heat-insulating composite material prepared in the present invention;
[0042] Figure 3 It is a bar chart of peel strength of composite materials prepared in the examples and comparative examples of the present invention in performance tests;
[0043] Figure 4 It is a bar graph of the infrared blocking rate and ultraviolet blocking rate of the composite materials prepared in the embodiments and comparative examples of the present invention in the performance test;
[0044] In the figure:
[0045] 1. Surface layer material; 2. Middle layer material; 3. Surface layer / middle layer composite material; 4. Adhesive layer material. DETAILED DESCRIPTION
[0046] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0047] Example 1
[0048] This embodiment discloses a method for preparing a sunscreen and heat-insulating composite material, comprising the following steps:
[0049] Step 1: preparing the surface layer / middle layer composite material and the adhesive layer material;
[0050] The surface layer / middle layer composite material is prepared by the following steps:
[0051] Step (1), mixing polyethylene glycol and nano zinc oxide, dispersing at a speed of 3000 r / min for 20 min, adding 2,4-diphenylcyclobutane-1,3-dicarboxylic acid, benzophenone-4,4-dicarboxylic acid and stannous octoate, the molar ratio of polyethylene glycol, 2,4-diphenylcyclobutane-1,3-dicarboxylic acid and benzophenone-4,4-dicarboxylic acid is 5:1.5:3.5, the amount of nano zinc oxide added is 8% of the mass of polyethylene glycol, and the amount of stannous octoate added is 3% of the mass of polyethylene glycol, reacting at a temperature of 175° C. in a nitrogen atmosphere for 5 h, and after the reaction is completed, continuing the reaction at a vacuum degree of 220 Pa and a temperature of 200° C. for 1.5 h, and after the reaction is completed, obtaining a zinc oxide / copolyester composite material;
[0052] The zinc oxide / copolyester composite material and polyethylene terephthalate were mixed in a mass ratio of 40:50, melt-extruded at a temperature of 270° C. by a twin-screw extruder, placed in a mold, hot-pressed into a film at a pressure of 5 MPa and a temperature of 270° C. by a flat vulcanizer, and quenched to obtain an intermediate layer material with a thickness of 90 μm;
[0053] Step (2), epoxy acrylate, γ-methacryloxypropyl trimethoxysilane, hexafluorobutyl acrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, photoinitiator, and acetone are uniformly mixed in a mass ratio of 100:9:7:13:13:3.5:23 to obtain a surface layer material, the surface layer material is coated on one side of the middle layer material, and light-cured under ultraviolet light with a wavelength of 405 nm at a temperature of 80° C. for 2 minutes to obtain a surface layer / middle layer composite material with a thickness of 95 μm;
[0054] The adhesive layer material is prepared by the following steps:
[0055] Step (1), mixing hexafluorobutanol, isophorone diisocyanate, dibutyltin dilaurate and acetone, reacting for 3.5 hours in a nitrogen atmosphere at 75°C, cooling to room temperature after the reaction, adding diethanolamine, the molar ratio of hexafluorobutanol, isophorone diisocyanate and diethanolamine is 1:1:0.9, the amount of dibutyltin dilaurate added is 2.5% of the mass of hexafluorobutanol, the amount of acetone added is 55% of the mass of hexafluorobutanol, and the reaction is continued at room temperature for 25 minutes. After the reaction is completed, the solvent acetone is removed by rotary evaporation at 45°C to obtain a fluorine-containing diol;
[0056] Step (2), mixing isophorone diisocyanate, polycarbonate diol and acetone, reacting for 2 hours at 70° C. in a nitrogen atmosphere, adding dibutyltin dilaurate, fluorinated diol and S-binaphthol after the reaction, continuing to react for 4 hours at 70° C., cooling to 50° C. after the reaction, adding p-hydroxyanisole and hydroxyethyl acrylate in sequence, reacting again for 3 hours at 50° C., and removing the solvent acetone by rotary evaporation at 40° C. to obtain polyurethane acrylate; wherein the mass ratio of isophorone diisocyanate, polycarbonate diol, fluorinated diol, S-binaphthol, dibutyltin dilaurate, acetone, p-hydroxyanisole and hydroxyethyl acrylate is 110:150:75:28:7:200:1.5:15;
[0057] Step (3), mixing polyurethane acrylate, heat insulation additive, maleic anhydride modified polyvinyl butyral, trimethylolpropane triacrylate, 4-(N-maleimido) benzophenone, and acetone at a mass ratio of 100:8:10:25:2:30 at 30° C. for 45 minutes to obtain a glue layer material;
[0058] The thermal insulation additive is prepared by the following steps:
[0059] 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane was mixed and dissolved with tetrahydrofuran, and a 37 wt % aqueous formaldehyde solution was added under a nitrogen atmosphere at 0°C, and the mixture was stirred for 0.5 h. A catechol solution prepared by mixing catechol and tetrahydrofuran in a mass ratio of 1:20 was added dropwise. The mass ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetrahydrofuran, 37 wt % aqueous formaldehyde solution and catechol solution was 2.5:90:3.2:38, and the addition time was 15 min. min, after the addition is completed, react at 60°C for 6h, after the reaction is completed, remove the solvent tetrahydrofuran by rotary evaporation at 40°C to obtain a crude reaction product, add toluene and water in an amount 4 times the mass of the crude reaction product in sequence, separate the liquids, take the organic phase, add saturated sodium bicarbonate aqueous solution and saturated sodium chloride aqueous solution in an amount 4 times the mass of the crude reaction product in sequence, wash three times, separate the liquids, take the washed organic phase, add 22wt% of anhydrous sodium sulfate to the washed organic phase, dry it, filter, take the filtrate, and remove the solvent by rotary evaporation at 75°C to obtain siloxane benzoxazine;
[0060] Nano copper sulfide, siloxane benzoxazine, dimethyl silicone oil and dichloromethane were mixed in a mass ratio of 7:3:10:20, ultrasonically dispersed for 15 minutes, reacted at 140°C for 5 hours, and continued to react at 175°C for 1.5 hours. After the reaction, cooled to room temperature, filtered, and the filter cake was taken, and dichloromethane 5 times the mass of the filter cake was added for washing, and dried at 50°C for 24 hours to obtain a thermal insulation additive;
[0061] Wherein, the maleic anhydride modified polyvinyl butyral is prepared by the following steps:
[0062] Polyvinyl butyral, maleic anhydride, N,N-dimethylbenzylamine and acetone were mixed in a mass ratio of 21:11:0.3:55, and reacted at 75°C for 4.5 hours. After the reaction was completed, the solvent acetone was removed by rotary evaporation at 45°C to obtain maleic anhydride-modified polyvinyl butyral;
[0063] Step 2: Apply a 15 μm thick adhesive layer material on the side of the surface / middle layer composite material away from the surface material (i.e., the side where the middle layer material is not coated with the surface material) at a coating speed of 5 m / min. After coating, dry at 40°C for 16 hours to obtain a sun-proof and heat-insulating composite material.
[0064] Example 2
[0065] This embodiment discloses a method for preparing a sunscreen and heat-insulating composite material, comprising the following steps:
[0066] Step 1: preparing the surface layer / middle layer composite material and the adhesive layer material;
[0067] The surface layer / middle layer composite material is prepared by the following steps:
[0068] Step (1), mixing polyethylene glycol and nano zinc oxide, dispersing at a speed of 3200 r / min for 15 min, adding 2,4-diphenylcyclobutane-1,3-dicarboxylic acid, benzophenone-4,4-dicarboxylic acid and stannous octoate, the molar ratio of polyethylene glycol, 2,4-diphenylcyclobutane-1,3-dicarboxylic acid and benzophenone-4,4-dicarboxylic acid is 5:1.4:3.6, the amount of nano zinc oxide added is 8% of the mass of polyethylene glycol, and the amount of stannous octoate added is 3% of the mass of polyethylene glycol, reacting in a nitrogen atmosphere at a temperature of 175° C. for 4.5 h, and after the reaction is completed, continuing to react at a vacuum degree of 230 Pa and a temperature of 210° C. for 1 h, and after the reaction is completed, obtaining a zinc oxide / copolyester composite material;
[0069] The zinc oxide / copolyester composite material and polyethylene terephthalate were mixed in a mass ratio of 43:50, melt-extruded at a temperature of 273°C by a twin-screw extruder, placed in a mold, hot-pressed into a film at a pressure of 6 MPa and a temperature of 275°C by a flat vulcanizer, and quenched to obtain an intermediate layer material with a thickness of 93 μm;
[0070] Step (2), coating the surface layer material on one side of the middle layer material. The preparation of the surface layer material is the same as that in Example 1. The surface layer material is photocured under ultraviolet light with a wavelength of 405 nm and a temperature of 85° C. for 1.5 min to obtain a surface layer / middle layer composite material with a thickness of 98 μm.
[0071] The adhesive layer material is prepared by the following steps:
[0072] Step (1), the preparation of fluorinated diol is the same as in Example 1;
[0073] Step (2), mixing isophorone diisocyanate, polycarbonate diol and acetone, reacting for 1.5 hours in a nitrogen atmosphere at 75°C, adding dibutyltin dilaurate, fluorinated diol and S-binaphthol after the reaction, continuing to react for 3.5 hours at 75°C, cooling to 55°C after the reaction, adding p-hydroxyanisole and hydroxyethyl acrylate in sequence, reacting again at 55°C for 2 hours, and removing the solvent acetone by rotary evaporation at 45°C to obtain polyurethane acrylate; wherein the mass ratio of isophorone diisocyanate, polycarbonate diol, fluorinated diol, S-binaphthol, dibutyltin dilaurate, acetone, p-hydroxyanisole and hydroxyethyl acrylate is 113:153:76:29:7.3:205:1.6:16;
[0074] Step (3), mixing polyurethane acrylate, thermal insulation additive, maleic anhydride modified polyvinyl butyral, trimethylolpropane triacrylate, 4-(N-maleimido) benzophenone, and acetone at a mass ratio of 100:8.5:12:26:2.3:35 at 35° C. for 40 minutes to obtain a glue layer material;
[0075] The preparation of maleic anhydride modified polyvinyl butyral is the same as that in Example 1; the thermal insulation additive is prepared by the following steps:
[0076] 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetrahydrofuran were mixed and dissolved, 37wt% formaldehyde aqueous solution was added in a nitrogen atmosphere at 1°C, stirred for 0.5h, and a catechol solution prepared by mixing catechol and tetrahydrofuran in a mass ratio of 1:20 was added dropwise, the mass ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetrahydrofuran, 37wt% formaldehyde aqueous solution, and catechol solution was 2.6:93:3.25:38.5, the dropping time was 15min, after the dropping was completed, the reaction was carried out at 65°C for 5.5h, after the reaction was completed, the solvent tetrahydrofuran was removed by rotary evaporation at 45°C, and purified to obtain siloxane-based benzoxazine; wherein the purification operation was the same as that in Example 1;
[0077] Nano copper sulfide, siloxane benzoxazine, dimethyl silicone oil and dichloromethane were mixed in a mass ratio of 7.3:2.7:15:25, ultrasonically dispersed for 15 minutes, reacted at 145°C for 4 hours, and then continued to react at 180°C for 1.5 hours. After the reaction, the mixture was cooled to room temperature, filtered, and the filter cake was taken. Dichloromethane 6 times the mass of the filter cake was added for washing, and dried at 55°C for 22 hours to obtain a thermal insulation additive;
[0078] Step 2: Apply a 16 μm thick adhesive layer material on the side of the surface / middle layer composite material away from the surface material (i.e., the side where the middle layer material is not coated with the surface material) at a coating speed of 6 m / min. After coating, dry at 45°C for 14 hours to obtain a sun-proof and heat-insulating composite material.
[0079] Example 3
[0080] This embodiment discloses a method for preparing a sunscreen and heat-insulating composite material, comprising the following steps:
[0081] Step 1: preparing the surface layer / middle layer composite material and the adhesive layer material;
[0082] The surface layer / middle layer composite material is prepared by the following steps:
[0083] Step (1), mixing polyethylene glycol and nano zinc oxide, dispersing at a speed of 3500r / min for 15min, adding 2,4-diphenylcyclobutane-1,3-dicarboxylic acid, benzophenone-4,4-dicarboxylic acid and stannous octoate, the molar ratio of polyethylene glycol, 2,4-diphenylcyclobutane-1,3-dicarboxylic acid and benzophenone-4,4-dicarboxylic acid is 5:1.3:3.7, the amount of nano zinc oxide added is 9% of the mass of polyethylene glycol, and the amount of stannous octoate added is 3% of the mass of polyethylene glycol, reacting in a nitrogen atmosphere at a temperature of 180°C for 4.5h, and after the reaction is completed, continuing the reaction at a vacuum degree of 230Pa and a temperature of 210°C for 1.3h, and after the reaction is completed, obtaining a zinc oxide / copolyester composite material;
[0084] The zinc oxide / copolyester composite material and polyethylene terephthalate were mixed in a mass ratio of 45:50, melt-extruded at a temperature of 273° C. by a twin-screw extruder, placed in a mold, hot-pressed into a film at a pressure of 8 MPa and a temperature of 275° C. by a flat vulcanizer, and quenched to obtain an intermediate layer material with a thickness of 95 μm;
[0085] Step (2), coating the surface layer material on one side of the middle layer material. The preparation of the surface layer material is the same as that in Example 1. The surface layer material is photocured under ultraviolet light with a wavelength of 405 nm and a temperature of 85° C. for 1.5 min to obtain a surface layer / middle layer composite material with a thickness of 100 μm.
[0086] The adhesive layer material is prepared by the following steps:
[0087] Step (1), the preparation of fluorinated diol is the same as in Example 1;
[0088] Step (2), mixing isophorone diisocyanate, polycarbonate diol and acetone, reacting for 1.8 hours in a nitrogen atmosphere at 75°C, adding dibutyltin dilaurate, fluorinated diol and S-binaphthol after the reaction, continuing to react for 3.5 hours at 75°C, cooling to 55°C after the reaction, adding p-hydroxyanisole and hydroxyethyl acrylate in sequence, reacting again at 55°C for 2.5 hours, and removing the solvent acetone by rotary evaporation at 45°C to obtain polyurethane acrylate; wherein the mass ratio of isophorone diisocyanate, polycarbonate diol, fluorinated diol, S-binaphthol, dibutyltin dilaurate, acetone, p-hydroxyanisole and hydroxyethyl acrylate is 115:155:78:30:7.5:210:1.8:18;
[0089] Step (3), mixing polyurethane acrylate, heat insulation additive, maleic anhydride modified polyvinyl butyral, trimethylolpropane triacrylate, 4-(N-maleimido) benzophenone, and acetone at a mass ratio of 100:9:13:28:2.5:35 at 35° C. for 40 minutes to obtain a glue layer material;
[0090] The preparation of maleic anhydride modified polyvinyl butyral is the same as that in Example 1; the thermal insulation additive is prepared by the following steps:
[0091] 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetrahydrofuran were mixed and dissolved, 37wt% formaldehyde aqueous solution was added in a nitrogen atmosphere at 1°C, stirred for 0.8h, and a catechol solution prepared by mixing catechol and tetrahydrofuran in a mass ratio of 1:20 was added dropwise, the mass ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetrahydrofuran, 37wt% formaldehyde aqueous solution, and catechol solution was 2.65:95:3.3:39, the dropping time was 18min, after the dropping was completed, the reaction was carried out at 65°C for 5.5h, after the reaction was completed, the solvent tetrahydrofuran was removed by rotary evaporation at 45°C, and the siloxane-based benzoxazine was obtained; wherein the purification operation was the same as that in Example 1;
[0092] Nano copper sulfide, siloxane benzoxazine, dimethyl silicone oil and dichloromethane were mixed in a mass ratio of 7.5:2.5:15:25, ultrasonically dispersed for 18 minutes, reacted at 145°C for 4.5 hours, and continued to react at 180°C for 1.3 hours. After the reaction, cooled to room temperature, filtered, and the filter cake was taken, and dichloromethane 6 times the mass of the filter cake was added for washing, and dried at 55°C for 22 hours to obtain a thermal insulation additive;
[0093] Step 2: Apply an adhesive layer material with a thickness of 18 μm on the side of the surface / middle layer composite material away from the surface material (i.e., the side on which the middle layer material is not coated with the surface material) at a coating speed of 7 m / min. After coating, dry at 45°C for 14 hours to obtain a sun-proof and heat-insulating composite material.
[0094] Example 4
[0095] This embodiment discloses a method for preparing a sunscreen and heat-insulating composite material, comprising the following steps:
[0096] Step 1: preparing the surface layer / middle layer composite material and the adhesive layer material;
[0097] The surface layer / middle layer composite material is prepared by the following steps:
[0098] Step (1), mixing polyethylene glycol and nano zinc oxide, dispersing at a speed of 3800 r / min for 15 min, adding 2,4-diphenylcyclobutane-1,3-dicarboxylic acid, benzophenone-4,4-dicarboxylic acid and stannous octoate, the molar ratio of polyethylene glycol, 2,4-diphenylcyclobutane-1,3-dicarboxylic acid and benzophenone-4,4-dicarboxylic acid is 5:1.1:3.9, the amount of nano zinc oxide added is 10% of the mass of polyethylene glycol, and the amount of stannous octoate added is 3% of the mass of polyethylene glycol, reacting in a nitrogen atmosphere at a temperature of 185° C. for 4.5 h, and after the reaction is completed, continuing the reaction at a vacuum degree of 230 Pa and a temperature of 210° C. for 1.5 h, and after the reaction is completed, obtaining a zinc oxide / copolyester composite material;
[0099] The zinc oxide / copolyester composite material and polyethylene terephthalate were mixed in a mass ratio of 48:50, melt-extruded at a temperature of 273° C. by a twin-screw extruder, placed in a mold, hot-pressed into a film at a pressure of 9 MPa and a temperature of 275° C. by a flat vulcanizer, and quenched to obtain an intermediate layer material with a thickness of 98 μm;
[0100] Step (2), coating the surface layer material on one side of the middle layer material. The preparation of the surface layer material is the same as that in Example 1. The surface layer material is photocured under ultraviolet light with a wavelength of 405 nm and a temperature of 85° C. for 1.5 min to obtain a surface layer / middle layer composite material with a thickness of 103 μm.
[0101] The adhesive layer material is prepared by the following steps:
[0102] Step (1), the preparation of fluorinated diol is the same as in Example 1;
[0103] Step (2), mixing isophorone diisocyanate, polycarbonate diol and acetone, reacting for 2 hours at 75°C in a nitrogen atmosphere, adding dibutyltin dilaurate, fluorinated diol and S-binaphthol after the reaction, continuing to react for 3.5 hours at 75°C, cooling to 50°C after the reaction, adding p-hydroxyanisole and hydroxyethyl acrylate in sequence, reacting again for 3 hours at 50°C, and removing the solvent acetone by rotary evaporation at 45°C to obtain polyurethane acrylate; wherein the mass ratio of isophorone diisocyanate, polycarbonate diol, fluorinated diol, S-binaphthol, dibutyltin dilaurate, acetone, p-hydroxyanisole and hydroxyethyl acrylate is 118:158:79:31:7.8:215:1.9:19;
[0104] Step (3), mixing polyurethane acrylate, heat insulation additive, maleic anhydride modified polyvinyl butyral, trimethylolpropane triacrylate, 4-(N-maleimido) benzophenone, and acetone at a mass ratio of 100:9.5:14:29:2.8:35 at 40° C. for 30 minutes to obtain a glue layer material;
[0105] The preparation of maleic anhydride modified polyvinyl butyral is the same as that in Example 1; the thermal insulation additive is prepared by the following steps:
[0106] 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetrahydrofuran were mixed and dissolved, 37wt% formaldehyde aqueous solution was added in a nitrogen atmosphere at 1°C, stirred for 1h, and a catechol solution prepared by mixing catechol and tetrahydrofuran in a mass ratio of 1:20 was added dropwise, the mass ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetrahydrofuran, 37wt% formaldehyde aqueous solution, and catechol solution was 2.7:98:3.4:39.5, the dropping time was 15min, after the dropping was completed, the reaction was carried out at 70°C for 5.5h, after the reaction was completed, the solvent tetrahydrofuran was removed by rotary evaporation at 45°C, and the siloxane-based benzoxazine was obtained; wherein the purification operation was the same as that in Example 1;
[0107] Nano copper sulfide, siloxane benzoxazine, dimethyl silicone oil and dichloromethane were mixed in a mass ratio of 7.8:2.2:15:25, ultrasonically dispersed for 20 minutes, reacted at 145°C for 4.5 hours, and continued to react at 185°C for 1 hour. After the reaction, cooled to room temperature, filtered, and the filter cake was taken, and dichloromethane 6 times the mass of the filter cake was added for washing, and dried at 55°C for 22 hours to obtain a thermal insulation additive;
[0108] Step 2: Apply a 19 μm thick adhesive layer material on the side of the surface / middle layer composite material away from the surface material (i.e., the side where the middle layer material is not coated with the surface material) at a coating speed of 8 m / min. After coating, dry at 45°C for 14 hours to obtain a sun-proof and heat-insulating composite material.
[0109] Example 5
[0110] This embodiment discloses a method for preparing a sunscreen and heat-insulating composite material, comprising the following steps:
[0111] Step 1: preparing the surface layer / middle layer composite material and the adhesive layer material;
[0112] The surface layer / middle layer composite material is prepared by the following steps:
[0113] Step (1), mixing polyethylene glycol and nano zinc oxide, dispersing at a speed of 4000 r / min for 10 minutes, adding 2,4-diphenylcyclobutane-1,3-dicarboxylic acid, benzophenone-4,4-dicarboxylic acid and stannous octoate, the molar ratio of polyethylene glycol, 2,4-diphenylcyclobutane-1,3-dicarboxylic acid and benzophenone-4,4-dicarboxylic acid is 5:1:4, the amount of nano zinc oxide added is 10% of the mass of polyethylene glycol, and the amount of stannous octoate added is 3% of the mass of polyethylene glycol, reacting in a nitrogen atmosphere at a temperature of 185° C. for 4 hours, and after the reaction is completed, continuing to react at a vacuum degree of 240 Pa and a temperature of 220° C. for 1 hour, and after the reaction is completed, obtaining a zinc oxide / copolyester composite material;
[0114] The zinc oxide / copolyester composite material and polyethylene terephthalate were mixed at a mass ratio of 50:50, melt-extruded at a temperature of 275° C. through a twin-screw extruder, placed in a mold, hot-pressed into a film at a pressure of 10 MPa and a temperature of 280° C. through a flat vulcanizer, and quenched to obtain an intermediate layer material with a thickness of 100 μm;
[0115] Step (2), coating the surface layer material on one side of the middle layer material. The preparation of the surface layer material is the same as that in Example 1. The surface layer material is photocured under ultraviolet light with a wavelength of 405 nm and a temperature of 90° C. for 1 min to obtain a surface layer / middle layer composite material with a thickness of 105 μm.
[0116] The adhesive layer material is prepared by the following steps:
[0117] Step (1), the preparation of fluorinated diol is the same as in Example 1;
[0118] Step (2), mixing isophorone diisocyanate, polycarbonate diol and acetone, reacting for 1.5 hours in a nitrogen atmosphere at 80°C, adding dibutyltin dilaurate, fluorinated diol and S-binaphthol after the reaction, continuing the reaction at 80°C for 3 hours, cooling to 60°C after the reaction, adding p-hydroxyanisole and hydroxyethyl acrylate in sequence, reacting again at 60°C for 2 hours, and removing the solvent acetone by rotary evaporation at 50°C to obtain polyurethane acrylate; wherein the mass ratio of isophorone diisocyanate, polycarbonate diol, fluorinated diol, S-binaphthol, dibutyltin dilaurate, acetone, p-hydroxyanisole and hydroxyethyl acrylate is 120:160:80:33:8:220:2:20;
[0119] Step (3), mixing polyurethane acrylate, thermal insulation additive, maleic anhydride modified polyvinyl butyral, trimethylolpropane triacrylate, 4-(N-maleimido) benzophenone, and acetone at a mass ratio of 100:10:15:30:3:40 at 40° C. for 30 minutes to obtain a glue layer material;
[0120] The preparation of maleic anhydride modified polyvinyl butyral is the same as that in Example 1; the thermal insulation additive is prepared by the following steps:
[0121] 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetrahydrofuran are mixed and dissolved, 37wt% formaldehyde aqueous solution is added in a nitrogen atmosphere at 2°C, stirred for 1h, and a catechol solution prepared by mixing catechol and tetrahydrofuran in a mass ratio of 1:20 is added dropwise, the mass ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetrahydrofuran, 37wt% formaldehyde aqueous solution, and catechol solution is 2.8:100:3.5:40, the dropping time is 20min, after the dropping is completed, the reaction is carried out at 70°C for 5h, after the reaction is completed, the solvent tetrahydrofuran is removed by rotary evaporation at 50°C, and the siloxane-based benzoxazine is obtained; wherein the purification operation is the same as that in Example 1;
[0122] Nano copper sulfide, siloxane benzoxazine, dimethyl silicone oil and dichloromethane were mixed in a mass ratio of 8:2:20:30, ultrasonically dispersed for 20 minutes, reacted at 150°C for 4 hours, and then continued to react at 185°C for 1 hour. After the reaction, the mixture was cooled to room temperature, filtered, and the filter cake was taken. Dichloromethane 8 times the mass of the filter cake was added for washing, and dried at 60°C for 20 hours to obtain a thermal insulation additive.
[0123] Step 2: Apply a 20 μm thick adhesive layer material on the side of the surface / middle layer composite material away from the surface material (i.e., the side where the middle layer material is not coated with the surface material) at a coating speed of 10 m / min. After coating, dry at 50°C for 12 hours to obtain a sun-proof and heat-insulating composite material.
[0124] Comparative Example 1
[0125] This embodiment discloses a method for preparing a composite material, comprising the following steps:
[0126] Step 1: preparing the surface layer / middle layer composite material and the adhesive layer material;
[0127] The surface layer / middle layer composite material is prepared by the following steps:
[0128] Step (1), mixing polyethylene glycol and nano zinc oxide, dispersing at a speed of 3000 r / min for 20 min, adding 2,4-diphenylcyclobutane-1,3-dicarboxylic acid, benzophenone-4,4-dicarboxylic acid and stannous octoate, the molar ratio of polyethylene glycol, 2,4-diphenylcyclobutane-1,3-dicarboxylic acid and benzophenone-4,4-dicarboxylic acid is 5:1.5:3.5, the amount of nano zinc oxide added is 8% of the mass of polyethylene glycol, and the amount of stannous octoate added is 3% of the mass of polyethylene glycol, reacting at a temperature of 175° C. in a nitrogen atmosphere for 5 h, and after the reaction is completed, continuing the reaction at a vacuum degree of 220 Pa and a temperature of 200° C. for 1.5 h, and after the reaction is completed, obtaining a zinc oxide / copolyester composite material;
[0129] The zinc oxide / copolyester composite material and polyethylene terephthalate were mixed in a mass ratio of 40:50, melt-extruded at a temperature of 270° C. by a twin-screw extruder, placed in a mold, hot-pressed into a film at a pressure of 5 MPa and a temperature of 270° C. by a flat vulcanizer, and quenched to obtain an intermediate layer material with a thickness of 90 μm;
[0130] Step (2), coating the surface layer material on one side of the middle layer material. The preparation of the surface layer material is the same as that in Example 1. The surface layer material is photocured under ultraviolet light with a wavelength of 405 nm and a temperature of 80° C. for 2 min to obtain a surface layer / middle layer composite material with a thickness of 95 μm.
[0131] The adhesive layer material is prepared by the following steps:
[0132] Step (1), the preparation of fluorinated diol is the same as in Example 1;
[0133] Step (2), mixing isophorone diisocyanate, polycarbonate diol and acetone, reacting for 2 hours at 70° C. in a nitrogen atmosphere, adding dibutyltin dilaurate, fluorinated diol and S-binaphthol after the reaction, continuing to react for 4 hours at 70° C., cooling to 50° C. after the reaction, adding p-hydroxyanisole and hydroxyethyl acrylate in sequence, reacting again for 3 hours at 50° C., and removing the solvent acetone by rotary evaporation at 40° C. to obtain polyurethane acrylate; wherein the mass ratio of isophorone diisocyanate, polycarbonate diol, fluorinated diol, S-binaphthol, dibutyltin dilaurate, acetone, p-hydroxyanisole and hydroxyethyl acrylate is 110:150:75:28:7:200:1.5:15;
[0134] Step (3), mixing polyurethane acrylate, nano copper sulfide, maleic anhydride modified polyvinyl butyral, trimethylolpropane triacrylate, 4-(N-maleimido) benzophenone, and acetone at a mass ratio of 100:8:10:25:2:30 at 30° C. for 45 minutes to obtain a glue layer material;
[0135] Wherein, the preparation of maleic anhydride modified polyvinyl butyral is the same as that in Example 1;
[0136] Step 2: Coat the side of the surface / middle layer composite material away from the surface material (i.e., the side where the middle layer material is not coated with the surface material) with a thickness of 15 μm. The coating speed is 5 m / min. After coating, dry at 40°C for 16 hours to obtain a composite material.
[0137] Comparative Example 2
[0138] This embodiment discloses a method for preparing a composite material, comprising the following steps:
[0139] Step 1: preparing the surface layer / middle layer composite material and the adhesive layer material;
[0140] The surface layer / middle layer composite material is prepared by the following steps:
[0141] Step (1), mixing polyethylene glycol and nano zinc oxide, dispersing at a speed of 3000 r / min for 20 min, adding 2,4-diphenylcyclobutane-1,3-dicarboxylic acid, benzophenone-4,4-dicarboxylic acid and stannous octoate, the molar ratio of polyethylene glycol, 2,4-diphenylcyclobutane-1,3-dicarboxylic acid and benzophenone-4,4-dicarboxylic acid is 5:1.5:3.5, the amount of nano zinc oxide added is 8% of the mass of polyethylene glycol, and the amount of stannous octoate added is 3% of the mass of polyethylene glycol, reacting at a temperature of 175° C. in a nitrogen atmosphere for 5 h, and after the reaction is completed, continuing the reaction at a vacuum degree of 220 Pa and a temperature of 200° C. for 1.5 h, and after the reaction is completed, obtaining a zinc oxide / copolyester composite material;
[0142] The zinc oxide / copolyester composite material and polyethylene terephthalate were mixed in a mass ratio of 40:50, melt-extruded at a temperature of 270° C. by a twin-screw extruder, placed in a mold, hot-pressed into a film at a pressure of 5 MPa and a temperature of 270° C. by a flat vulcanizer, and quenched to obtain an intermediate layer material with a thickness of 90 μm;
[0143] Step (2), epoxy acrylate, γ-methacryloxypropyl trimethoxysilane, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, photoinitiator, and acetone are uniformly mixed in a mass ratio of 107:9:13:13:3.5:23 to obtain a surface layer material, the surface layer material is coated on one side of the middle layer material, and light-cured under ultraviolet light with a wavelength of 405 nm at a temperature of 80° C. for 2 minutes to obtain a surface layer / middle layer composite material with a thickness of 95 μm;
[0144] The adhesive layer material is prepared by the following steps:
[0145] Step (1), mixing isophorone diisocyanate, polycarbonate diol and acetone, reacting for 2 hours at 70° C. in a nitrogen atmosphere, adding dibutyltin dilaurate and S-binaphthol after the reaction, continuing to react for 4 hours at 70° C., cooling to 50° C. after the reaction, sequentially adding p-hydroxyanisole and hydroxyethyl acrylate, reacting again for 3 hours at 50° C., and removing the solvent acetone by rotary evaporation at 40° C. to obtain polyurethane acrylate; wherein the mass ratio of isophorone diisocyanate, polycarbonate diol, S-binaphthol, dibutyltin dilaurate, acetone, p-hydroxyanisole and hydroxyethyl acrylate is 110:200:28:7:200:1.5:15;
[0146] Step (2), mixing polyurethane acrylate, heat insulation additive, maleic anhydride modified polyvinyl butyral, trimethylolpropane triacrylate, 4-(N-maleimido) benzophenone, and acetone at a mass ratio of 100:8:10:25:2:30 at 30° C. for 45 minutes to obtain a glue layer material;
[0147] The preparation of maleic anhydride modified polyvinyl butyral is the same as that in Example 1; the thermal insulation additive is prepared by the following steps:
[0148] 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetrahydrofuran were mixed and dissolved, 37wt% formaldehyde aqueous solution was added under nitrogen atmosphere at 0°C, stirred for 0.5h, catechol solution prepared by mixing catechol and tetrahydrofuran in a mass ratio of 1:20 was added dropwise, the mass ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetrahydrofuran, 37wt% formaldehyde aqueous solution and catechol solution was 2.5:90:3.2:38, the dropping time was 15min, after the dropping was completed, the reaction was carried out at 60°C for 6h, after the reaction was completed, the solvent tetrahydrofuran was removed by rotary evaporation at 40°C, and purified to obtain siloxane-based benzoxazine; wherein the purification operation was the same as that in Example 1;
[0149] Nano copper sulfide, siloxane benzoxazine, dimethyl silicone oil and dichloromethane were mixed in a mass ratio of 7:3:10:20, ultrasonically dispersed for 15 minutes, reacted at 140°C for 5 hours, and continued to react at 175°C for 1.5 hours. After the reaction, cooled to room temperature, filtered, and the filter cake was taken, and dichloromethane 5 times the mass of the filter cake was added for washing, and dried at 50°C for 24 hours to obtain a thermal insulation additive;
[0150] Step 2: Coat the side of the surface / middle layer composite material away from the surface material (i.e., the side where the middle layer material is not coated with the surface material) with a thickness of 15 μm. The coating speed is 5 m / min. After coating, dry at 40°C for 16 hours to obtain a composite material.
[0151] Comparative Example 3
[0152] This embodiment discloses a method for preparing a composite material, comprising the following steps:
[0153] Step 1: preparing the surface layer / middle layer composite material and the adhesive layer material;
[0154] The surface layer / middle layer composite material is prepared by the following steps:
[0155] Step (1), melt-extrude polyethylene terephthalate at a temperature of 270° C. through a twin-screw extruder, place it in a mold, hot-press it into a film at a pressure of 5 MPa and a temperature of 270° C. through a flat vulcanizer, and quench it to obtain an intermediate layer material with a thickness of 90 μm;
[0156] Step (2), coating the surface layer material on one side of the middle layer material. The preparation of the surface layer material is the same as that in Example 1. The surface layer material is photocured under ultraviolet light with a wavelength of 405 nm and a temperature of 80° C. for 2 min to obtain a surface layer / middle layer composite material with a thickness of 95 μm.
[0157] The adhesive layer material is prepared by the following steps:
[0158] Step (1), the preparation of fluorinated diol is the same as in Example 1;
[0159] Step (2), mixing isophorone diisocyanate, polycarbonate diol and acetone, reacting for 2 hours at 70° C. in a nitrogen atmosphere, adding dibutyltin dilaurate, fluorinated diol and S-binaphthol after the reaction, continuing to react for 4 hours at 70° C., cooling to 50° C. after the reaction, adding p-hydroxyanisole and hydroxyethyl acrylate in sequence, reacting again for 3 hours at 50° C., and removing the solvent acetone by rotary evaporation at 40° C. to obtain polyurethane acrylate; wherein the mass ratio of isophorone diisocyanate, polycarbonate diol, fluorinated diol, S-binaphthol, dibutyltin dilaurate, acetone, p-hydroxyanisole and hydroxyethyl acrylate is 110:150:75:28:7:200:1.5:15;
[0160] Step (3), mixing polyurethane acrylate, heat insulation additive, maleic anhydride modified polyvinyl butyral, trimethylolpropane triacrylate, 4-(N-maleimido) benzophenone, and acetone at a mass ratio of 100:8:10:25:2:30 at 30° C. for 45 minutes to obtain a glue layer material;
[0161] The preparation of maleic anhydride modified polyvinyl butyral is the same as that in Example 1; the thermal insulation additive is prepared by the following steps:
[0162] 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetrahydrofuran were mixed and dissolved, 37wt% formaldehyde aqueous solution was added under nitrogen atmosphere at 0°C, stirred for 0.5h, catechol solution prepared by mixing catechol and tetrahydrofuran in a mass ratio of 1:20 was added dropwise, the mass ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetrahydrofuran, 37wt% formaldehyde aqueous solution and catechol solution was 2.5:90:3.2:38, the dropping time was 15min, after the dropping was completed, the reaction was carried out at 60°C for 6h, after the reaction was completed, the solvent tetrahydrofuran was removed by rotary evaporation at 40°C, and purified to obtain siloxane-based benzoxazine; wherein the purification operation was the same as that in Example 1;
[0163] Nano copper sulfide, siloxane benzoxazine, dimethyl silicone oil and dichloromethane were mixed in a mass ratio of 7:3:10:20, ultrasonically dispersed for 15 minutes, reacted at 140°C for 5 hours, and continued to react at 175°C for 1.5 hours. After the reaction, cooled to room temperature, filtered, and the filter cake was taken, and dichloromethane 5 times the mass of the filter cake was added for washing, and dried at 50°C for 24 hours to obtain a thermal insulation additive;
[0164] Step 2: Coat the side of the surface / middle layer composite material away from the surface material (i.e., the side where the middle layer material is not coated with the surface material) with a thickness of 15 μm. The coating speed is 5 m / min. After coating, dry at 40°C for 16 hours to obtain a composite material.
[0165] In the above embodiments and comparative examples: polyethylene glycol comes from Shanghai MacLean Biochemical Technology Co., Ltd., with an average molecular weight of 400 and a CAS number of 25322-68-3; nano zinc oxide comes from Shanghai Aladdin Biochemical Technology Co., Ltd., with a particle size of 40-60 nm and a CAS number of 1314-13-2; 2,4-diphenylcyclobutane-1,3-dicarboxylic acid comes from Beijing Bailingwei Technology Co., Ltd., with a CAS number of 4462-95-7; benzophenone-4,4-dicarboxylic acid comes from Shanghai Aladdin Biochemical Technology Co., Ltd., with a CAS number of 964-68-1; polyethylene terephthalate comes from Yuyao Ruijing Plastic Chemical Co., Ltd., with a model of PET CZ-302; epoxy acrylate comes from Allnex Resin Co., Ltd., with a model of EBECRYL 3600 modified epoxy acrylate; photoinitiator comes from Jiangsu Runfeng Synthetic Technology Co., Ltd., product name photoinitiator 1173, CAS number: 7374-98-5; polycarbonate diol comes from Shandong Duolian Chemical Co., Ltd., with an average molecular weight of 1000; S-binaphthol comes from Shanghai MacLean Biochemical Technology Co., Ltd., CAS number: 18531-99-2; 4-(N-maleimido)benzophenone comes from Shanghai MacLean Biochemical Technology Co., Ltd., CAS number: 92944-71-3; 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane comes from AlfaAesar, CAS number: 2469-55-8; nano copper sulfide comes from Hubei Langbowan Biomedicine Co., Ltd., specification empty shell sphere, wall thickness 20nm; polyvinyl butyral comes from Shanghai MacLean Biochemical Technology Co., Ltd., with an average molecular weight of 40000, CAS number: 63148-65-2.
[0166] Test example
[0167] The composite materials prepared in the above examples and comparative examples were tested for performance, and the specific test results are shown in Table 1:
[0168] Table 1
[0169]
[0170] The detection of each indicator in Table 1 is based on the following standards:
[0171] The peel strength is measured with reference to GB / T2792-2014 "Test method for peel strength of adhesive tape"; the water resistance is measured with reference to GB / T1733-1993 "Determination of water resistance of paint film", expressed by the peel strength retention rate, and the test time is 200h; the infrared blocking rate and ultraviolet blocking rate are measured with reference to GB / T2680-1994 "Determination of visible light transmittance, direct sunlight transmittance, total solar energy transmittance, ultraviolet transmittance and related window glass parameters of architectural glass", and the specific test method for infrared blocking rate is as follows: : In the near-infrared band of the solar spectrum within the range of 780nm-2500nm, the infrared spectral transmittance of the embodiment and the comparative example is tested by Agilent Cary5000 UV-Visible-Infrared spectrophotometer, and the infrared blocking rate is obtained after calculation; the specific testing method of the ultraviolet blocking rate is as follows: in the range of 300nm-380nm of the solar spectrum, the ultraviolet spectral transmittance of the embodiment and the comparative example is tested by Agilent Cary5000 UV-Visible-Infrared spectrophotometer, and the ultraviolet blocking rate is obtained after calculation.
[0172] It can be seen from the test results in Table 1 that the composite material prepared by the present invention has excellent anti-ultraviolet performance and heat insulation performance, and good water resistance and bonding performance.
[0173] The surface layer material is coated on one side of the middle layer material. Since the γ-methacryloxypropyltrimethoxysilane and hexafluorobutyl acrylate contained in the surface layer material have low surface energy, the hydrophobicity of the surface of the material can be improved. The polyurethane acrylate in the adhesive layer material introduces fluorinated diols and S-binaphthol in the preparation process. The fluorinated diols can improve the hydrophobicity. The S-binaphthol has a rigid structure of aromatic compounds and optical activity, which can reduce the infrared emissivity of the material and improve the heat resistance and heat insulation performance of the material. The heat insulation filler nano copper sulfide in the heat insulation additive has excellent heat insulation performance, and the polybenzoxazine structure has good heat resistance and is rich in phenolic hydroxyl groups, which can The nano copper sulfide in the adhesive layer material of Comparative Example 1 is not surface modified, the nano copper oxide has reduced dispersibility in the adhesive layer material, is easily agglomerated, and has poor compatibility with the resin matrix of the adhesive layer material, which affects the peel strength of the adhesive layer material and the thermal insulation performance of the composite material. Therefore, the peel strength and infrared blocking rate of Comparative Example 1 are lower than those of the embodiment. In Comparative Example 2, hexafluorobutyl acrylate and fluorinated diol are not added to the surface material and the adhesive layer material, and the hydrophobicity of the composite material is reduced. Therefore, the water resistance of Comparative Example 2 is not as good as that of the embodiment.
[0174] In the present invention, zinc oxide / copolyester composite materials are added when preparing the intermediate layer material. 2,4-diphenylcyclobutane-1,3-dicarboxylic acid has a double benzene ring structure, which can improve the ultraviolet shielding effect and heat resistance of the material. Benzophenone-4,4-dicarboxylic acid contains a benzophenone group with ultraviolet absorption effect. The two are introduced into the copolyester as polymerization monomers, which can synergize with the anti-ultraviolet nano zinc oxide to further improve the anti-ultraviolet performance and heat resistance of the zinc oxide / copolyester composite material. The intermediate layer material of comparative example 3 does not add the zinc oxide / copolyester composite material, and the anti-ultraviolet performance is reduced, so the ultraviolet blocking rate of comparative example 3 is lower than that of the embodiment.
[0175] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a sun-proof and heat-insulating composite material, characterized in that: The following steps are involved: Step 1: preparing the surface layer / middle layer composite material and the adhesive layer material; The surface layer / middle layer composite material is prepared by the following steps: Step (1), mixing the zinc oxide / copolyester composite material with polyethylene terephthalate, melt-extruding, hot-pressing into a film, and quenching to obtain an intermediate layer material; Step (2), coating the surface layer material on one side of the middle layer material, and light curing to obtain a surface layer / middle layer composite material; The adhesive layer material is prepared by the following steps: Step (1), mixing isophorone diisocyanate, polycarbonate diol and acetone, reacting, adding dibutyltin dilaurate, fluorinated diol and S-binaphthol after the reaction, continuing the reaction, cooling after the reaction, adding p-hydroxyanisole and hydroxyethyl acrylate in sequence, reacting again, and removing the solvent acetone by rotary evaporation after the reaction to obtain polyurethane acrylate; Step (2), mixing polyurethane acrylate, heat insulation additive, maleic anhydride modified polyvinyl butyral, trimethylolpropane triacrylate, 4-(N-maleimido) benzophenone, and acetone to obtain a glue layer material; Step 2: coating the adhesive layer material on the side of the surface layer / middle layer composite material away from the surface layer material, and drying after coating to obtain a sun-proof and heat-insulating composite material.
2. The method for preparing the sun-proof and heat-insulating composite material according to claim 1, characterized in that: When preparing the surface layer / middle layer composite material in step 1, in step (1): the zinc oxide / copolyester composite material is prepared by the following steps: The polyethylene glycol and nano zinc oxide are mixed and dispersed, 2,4-diphenylcyclobutane-1,3-dicarboxylic acid, benzophenone-4,4-dicarboxylic acid and stannous octoate are added, and the reaction is continued after the reaction is completed. After the reaction is completed, the zinc oxide / copolyester composite material is obtained; The molar ratio of polyethylene glycol, 2,4-diphenylcyclobutane-1,3-dicarboxylic acid and benzophenone-4,4-dicarboxylic acid is 5:1-1.5:3.5-4, the amount of nano zinc oxide added is 8-10% of the mass of polyethylene glycol, and the amount of stannous octoate added is 3% of the mass of polyethylene glycol; the reaction conditions are: reacting for 4-5 hours at a temperature of 175-185°C in a nitrogen atmosphere; and the continued reaction conditions are: continuing the reaction for 1-1.5 hours at a vacuum degree of 220-240Pa and a temperature of 200-220°C.
3. The method for preparing the sun-proof and heat-insulating composite material according to claim 1, characterized in that: When preparing the surface layer / middle layer composite material in step 1, in step (2): the surface layer material is prepared by the following steps: Epoxy acrylate, γ-methacryloxypropyl trimethoxysilane, hexafluorobutyl acrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, a photoinitiator, and acetone are uniformly mixed to obtain a surface material; Among them, the mass ratio of epoxy acrylate, γ-methacryloxypropyltrimethoxysilane, hexafluorobutyl acrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, photoinitiator and acetone is 100:8-10:6-8:10-15:10-15:3-4:20-25.
4. The method for preparing the sun-proof and heat-insulating composite material according to claim 1, characterized in that: When preparing the surface layer / middle layer composite material in step 1, in step (1): the mass ratio of the zinc oxide / copolyester composite material to the polyethylene terephthalate is 40-50:50; the melt extrusion conditions are: melt extrusion at a temperature of 270-275° C.; the hot pressing film forming conditions are: placing in a mold and hot pressing through a flat vulcanizer at a pressure of 5-10 MPa and a temperature of 270-280° C. to form a film; the thickness of the middle layer material is 90-100 μm; In step (2), the photocuring conditions are: photocuring for 1-2 minutes at 80-90° C. under ultraviolet light with a wavelength of 405 nm; the thickness of the surface layer / middle layer composite material is 95-105 μm.
5. The method for preparing the sun-proof and heat-insulating composite material according to claim 1, characterized in that: When preparing the adhesive layer material in step 1, in step (1): the fluorinated diol is prepared by the following steps: Hexafluorobutanol, isophorone diisocyanate, dibutyltin dilaurate and acetone are mixed evenly and reacted. After the reaction is completed, the temperature is lowered to room temperature, diethanolamine is added, and the reaction is continued. After the reaction is completed, the solvent acetone is removed by rotary evaporation to obtain a fluorinated diol; The molar ratio of hexafluorobutanol, isophorone diisocyanate and diethanolamine is 0.9-1:1:0.9-1, the amount of dibutyltin dilaurate added is 2-3% of the mass of hexafluorobutanol, and the amount of acetone added is 50-60% of the mass of hexafluorobutanol; the reaction conditions are: reacting for 3-4 hours at 70-80°C in a nitrogen atmosphere; and the continued reaction conditions are: continuing the reaction at room temperature for 20-30 minutes.
6. The method for preparing the sun-proof and heat-insulating composite material according to claim 1, characterized in that: When preparing the adhesive layer material in step 1, in step (2), the thermal insulation additive is prepared by the following steps: Mix and dissolve 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetrahydrofuran, add formaldehyde aqueous solution, stir, dropwise add catechol solution, react after the dropwise addition is complete, and after the reaction is complete, remove the solvent tetrahydrofuran by rotary evaporation, purify, and obtain siloxane-based benzoxazine; The mass ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetrahydrofuran, formaldehyde aqueous solution and catechol solution is 2.5-2.8:90-100:3.2-3.5:38-40; the formaldehyde aqueous solution is a 37wt% formaldehyde aqueous solution, and the addition conditions are: adding in a nitrogen atmosphere at a temperature of 0-2°C, and stirring for 0.5-1h after adding; the catechol solution is prepared by mixing catechol and tetrahydrofuran at a mass ratio of 1:20, and the dropwise addition time is 15-20min; when preparing siloxane-based benzoxazine, the reaction conditions are: reacting at a temperature of 60-70°C for 5-6h; The nano copper sulfide, siloxane benzoxazine, dimethyl silicone oil and dichloromethane are mixed, ultrasonically dispersed, reacted, and after the reaction is completed, the reaction is continued. After the reaction is completed, the reaction is cooled, filtered, washed and dried to obtain a heat insulation additive; Among them, the mass ratio of nano copper sulfide, siloxane benzoxazine, dimethyl silicone oil and dichloromethane is 7-8:2-3:10-20:20-30; when preparing the thermal insulation additive, the reaction conditions are: react at a temperature of 140-150°C for 4-5h, and the continued reaction conditions are: continue to react at a temperature of 175-185°C for 1-1.5h.
7. The method for preparing the sun-proof and heat-insulating composite material according to claim 1, characterized in that: When preparing the adhesive layer material in step 1, in step (2), the maleic anhydride-modified polyvinyl butyral is prepared by the following steps: Polyvinyl butyral, maleic anhydride, N,N-dimethylbenzylamine and acetone are mixed and reacted, and after the reaction is completed, the solvent acetone is removed by rotary evaporation to obtain maleic anhydride modified polyvinyl butyral; The mass ratio of polyvinyl butyral, maleic anhydride, N,N-dimethylbenzylamine and acetone is 20-22:10-12:0.3:50-60; and the reaction conditions are: reacting at a temperature of 70-80° C. for 4-5 hours.
8. The method for preparing the sun-proof and heat-insulating composite material according to claim 1, characterized in that: When preparing the adhesive layer material in the step 1, in step (1), the mass ratio of isophorone diisocyanate, polycarbonate diol, fluorinated diol, S-binaphthol, dibutyltin dilaurate, acetone, p-hydroxyanisole, and hydroxyethyl acrylate is 110-120:150-160:75-80:28-33:7-8:200-220:1.5-2:15-20; the reaction conditions are: reacting at a temperature of 70-80°C in a nitrogen atmosphere for 1.5-2h; continuing the reaction conditions are: continuing the reaction at a temperature of 70-80°C for 3-4h; and re-reacting conditions are: reacting again at a temperature of 50-60°C for 2-3h. In step (2), the mass ratio of polyurethane acrylate, thermal insulation additive, maleic anhydride modified polyvinyl butyral, trimethylolpropane triacrylate, 4-(N-maleimido)benzophenone and acetone is 100:8-10:10-15:25-30:2-3:30-40.
9. The method for preparing the sun-proof and heat-insulating composite material according to claim 1, characterized in that: In the step 2: the coating speed is 5-10 m / min, and the thickness of the adhesive layer material is 15-20 μm.
10. A sun-proof and heat-insulating composite material prepared by the method for preparing a sun-proof and heat-insulating composite material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Anti-ultraviolet high-heat-insulation window film
CN102765224A